2015
DOI: 10.15537/smj.2015.11.12462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mini-implant sites in the posterior maxilla using traditional radiographs and cone-beam computed tomography

Abstract: Objectives:To evaluate the accuracy of using routine 2-dimensional (2D) radiographs (panoramic and periapical) when evaluating the position of orthodontic temporary anchorage devices (mini-implants) in the maxilla, and to compare the results to 3-dimensional cone-beam computed tomography (CBCT).Methods:This cross-sectional study was conducted at King Abdulaziz University, Faculty of Dentistry, Jeddah, Kingdom of Saudi Arabia from February 2014 to January 2015. Panoramic and periapical radiographs were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Although the radiation exposure of standard digital panoramic radiography was found to be much less compared to CBCT, some cases require CBCT scan for more accurate measurements. [14] It is the clinician's responsibility to determine the need for a more extensive radiographic study for the best outcome with the least possible risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the radiation exposure of standard digital panoramic radiography was found to be much less compared to CBCT, some cases require CBCT scan for more accurate measurements. [14] It is the clinician's responsibility to determine the need for a more extensive radiographic study for the best outcome with the least possible risk.…”
Section: Resultsmentioning
confidence: 99%
“…Bone width can be determined clinically using bone-mapping techniques or by cone-beam computerized tomography (CBCT) scan which has been shown to be more accurate than panoramic radiographs. [14] Hence, careful radiographic and clinical measurements are essential to determine the size of the implant for the intended site.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy of PAR for determining the final position of OMI is lower when compared with CBCT. 17 , 19 The present study did not aim to test accuracy, however, results showed great variability suggesting low reliability of these radiographic methods (PAR, VBW and OC) for this type of evaluation. In general, it was clear that additional radiographs might influence the interpretation of the OMI final position, however, a definite pattern showing which exam modality overestimates or underestimates distances was not observed.…”
Section: Discussionmentioning
confidence: 75%
“…Correct positioning of orthodontic mini-implants (OMI) is one of the most important factors associated to their success rate. 1 - 5 Several methods 6 - 17 have been used to assess the position of these devices. Periapical radiograph (PAR) is the most used imaging modality for post-placement evaluation of OMI position, 18 despite its limitations and the lack of studies to actually support this recommendation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation